Controllable synthesis of phosphate-modified BiPO4 nanorods with high photocatalytic activity: surface hydroxyl groups concentrations effects. Issue 121 (20th November 2015) - Li, Yan; Wang, Yawen; Huang, Yu; Cao, Junji; Ho, Wingkei; Lee, Shuncheng; Fan, Caimei
Abstract : Surface modification by phosphate efficiently improves the photocatalytic performance of BiPO4 for the degradation of methylene orange (MO), by enhancing the concentration of surface hydroxyl groups and improving its hydrophilicity. Abstract : Surface properties of photocatalysts are crucial to improve their efficiency in the removal of wastewater pollutants. In this study, phosphate-modified BiPO4 photocatalysts with different PO4 3− /Bi molar ratios were controllably synthesized through a one-pot hydrothermal method. The concentrations of surface hydroxyl groups on BiPO4 samples can be tuned by adjusting the PO4 3− /Bi 3+ molar ratios. XRD results showed that surface modification by phosphate could boost the crystallinity of BiPO4, which was beneficial to photocatalytic performance. XPS and IR spectra revealed that PO4 3− modified only the surface of BiPO4 . The optical absorption of phosphate-modified BiPO4 samples showed an obvious blue shift compared with that of bare BiPO4 . Photocatalytic activities of the as-prepared samples were evaluated by the decomposition of methylene orange (MO) under ultraviolet light and simulated solar-light irradiation. Experimental results demonstrated that the photocatalytic performance of the modified samples significantly improved after the BiPO4 surface was modified by different amounts of PO4 3− . Both an indirect scavenger method and an electron spin resonance method were adopted to determine the production and intensity of free radicals during photocatalytic degradation. Results suggested that MO was removed predominantly through oxidation by OH radicals, as confirmed by theoretical calculations. Moreover, the mechanism of photocatalytic degradation of MO over the as-prepared phosphate-modified BiPO4 was proposed.